Alteration of Cortical Functional Connectivity as a Result of Traumatic Brain Injury Revealed by Graph Theory, ICA, and sLORETA Analyses of EEG Signals - Cao, C. (2009)
In this paper, a novel approach to examine the cortical functional connectivity using multichannel electroen-cephalographic (EEG) signals is proposed. First we utilized independent component analysis (ICA) to transform multichannel EEG recordings into independent processes and then applied source reconstruction algorithm [i.e., standardize low resolution brain electromagnetic (sLORETA)] to identify the cortical regions of interest (ROIs). Second, we performed a graph theory analysis of the bipartite network composite of ROIs and independent processes to assess the connectivity between ROIs. We applied this proposed algorithm and compared the functional connectivity network properties under resting state condition using 29 student-athletes prior to and shortly after sport-related mild traumatic brain injury (MTBI). The major findings of interest are the following. There was 1) alterations in vertex degree at frontal and occipital regions in subjects suffering from MTBI, (p < 0.05); 2) a significant decrease in the long-distance connectivity and significant increase in the short-distance connectivity as a result of MTBI, (p < 0.05); 3) a departure from small-world network configuration in MTBI subjects. These major findings are discussed in relation to current debates regarding the brain functional connectivity within and between local and distal regions both in normal controls in pathological subjects.